Adsorption Competition between H+ and Cd2+ Ions Toward Active Sites on Ionic Imprinted Mercapto-Silica Hybrid - Buhani Buhani (EKSAKTA: Journal of Sciences and Data Analysis, 2011)
Adsorption process on Cd2+ionic  imprinted mercapto-silica hybrid material  (Cd(II)-IIP HMS) has been carried out with studying an adsorption competition between ion H+ and Cd2+ ion upon active sites of Cd(II)-IIP HMS material.  Characterization of surface material was based on specific surface area, total volume, and porous diameter.  Cd(II)-IIP HMS material with template ionic concentration of each 0.107; 0.214; 0.429; 0.658 mmol g-1 shows  that adsorption model  is relatively similar, the higher of H+ ion competed,  the  lower of adsorption capacity of Cd(II)-IIP HMS material upon Cd2+ ion.  Keywords: adsorption, active site, mercapto-silica hybrid, ionic imprinted